If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) + -4x + -2x + -6 = -9 Reorder the terms: 3(-1 + 2x) + -4x + -2x + -6 = -9 (-1 * 3 + 2x * 3) + -4x + -2x + -6 = -9 (-3 + 6x) + -4x + -2x + -6 = -9 Reorder the terms: -3 + -6 + 6x + -4x + -2x = -9 Combine like terms: -3 + -6 = -9 -9 + 6x + -4x + -2x = -9 Combine like terms: 6x + -4x = 2x -9 + 2x + -2x = -9 Combine like terms: 2x + -2x = 0 -9 + 0 = -9 -9 = -9 Add '9' to each side of the equation. -9 + 9 = -9 + 9 Combine like terms: -9 + 9 = 0 0 = -9 + 9 Combine like terms: -9 + 9 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 676X+567+4056X+1152Y-382716=0 | | 3(3w+7)=68 | | 5(-3.25)+5(-6.75)= | | (5/9)^3×(18/25)^2 | | -2(-10+x)=26 | | 49.50/16.50 | | 3/35.46=6/x | | 10w+3=83 | | -(2x+4)+8x+(-6)= | | X-209=0 | | 1.6*10^7/3.5*10^-2 | | y-12=-1(x-6) | | 16k+12h-1h+10k-3k= | | 5(x+y)+3(y+1)= | | 6/10=12/x | | 16+1-16= | | 6-3s=-6 | | (2)x+15=3x+20 | | 15.36=y | | g(-x)=3x^2-2x+6 | | 22+6=180 | | 5x10^6/4x10^4 | | 3y+1-5(-3y-1)=2(y-3) | | 5x10^6/4x10^5 | | 18+7s=15.8 | | 9*x^2+4*y^2-24y=0 | | (5x+6)=(4x+11) | | -3x+12=3x | | (2)2x=6x-20 | | 2a-7=14a | | 3n+7-7n=34-12n+21 | | 24x^3-78x^2-24x= |